(untitled) (Journal of Atomic and Molecular Sciences, 2015)
The vector correlations between products and reagents for the chemical reactions O^++H_2/D_2/T_2 at different collision energies (1.0eV-2.8eV) have been studied by means of the quasi-classical trajectory (QCT) method based on the RODRIGO potential energy surface(PES) [Rodrigo et al 2004 J. Chem. Phys. 120 4705]. The four generalized polarization-dependent differential cross-sections (PDDCSs)(2π/σ)(dσ_00/dω_t), (2π/σ)(dσ_20/dω_t), (2π/σ)(dσ_22+/dω_t) and (2π/σ)(dσ_21-/dω_t) have also been calculated at seven different collision energies respectively. The isotope effect comparing with the effect of collision energies has been discussed further. The results indicate that the reaction is sensitive to the mass factors. Meanwhile the collision energies have a greater effect than the mass factors.